Considering sex as a biological variable in preclinical research. Issue 1 (28th September 2016) - Miller, Leah R.; Marks, Cheryl; Becker, Jill B.; Hurn, Patricia D.; Chen, Wei‐Jung; Woodruff, Teresa; McCarthy, Margaret M.; Sohrabji, Farida; Schiebinger, Londa; Wetherington, Cora Lee; Makris, Susan; Arnold, Arthur P.; et al.
Abstract : In June 2015, the National Institutes of Health (NIH) released a Guide notice (NOT‐OD‐15–102) that highlighted the expectation of the NIH that the possible role of sex as a biologic variable be factored into research design, analyses, and reporting of vertebrate animal and human studies. Anticipating these guidelines, the NIH Office of Research on Women's Health, in October 2014, convened key stakeholders to discuss methods and techniques for integrating sex as a biologic variable in preclinical research. The workshop focused on practical methods, experimental design, and approaches to statistical analyses in the use of both male and female animals, cells, and tissues in preclinical research. Workshop participants also considered gender as a modifier of biology. This article builds on the workshop and is meant as a guide to preclinical investigators as they consider methods and techniques for inclusion of both sexes in preclinical research and is not intended to prescribe exhaustive/specific approaches for compliance with the new NIH policy.—Miller, L. R., Marks, C., Becker, J.B., Hurn, P.D., Chen, W.‐J., Woodruff, T., McCarthy, M.M., Sohrabji, F., Schiebinger, L., Wetherington, C.L., Makris, S., Arnold, A. P., Einstein, G., Miller, V. M., Sandberg, K., Maier, S., Cornelison, T. L., Clayton, J. A. Considering sex as a biological variable in preclinical research. FASEB J. 31, 29–34 (2017) www.fasebj.org